2020
DOI: 10.3390/cancers12020397
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Postoperative Seizure Outcome in Low Grade Glioma: From Volumetric Analysis to Molecular Stratification

Abstract: The importance of the extent of resection (EOR) has been widely demonstrated as the main predictor for survival, nevertheless its effect on tumor related epilepsy is less investigated. A total of 155 patients were enrolled after a first-line surgery for supratentorial Diffuse Low Grade Gliomas (DLGGs). Postoperative seizure outcome was analyzed stratifying the results by tumor volumetric data and molecular markers according to 2016 WHO classification. Receiver operating characteristic (ROC) curves were compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 44 publications
2
37
0
Order By: Relevance
“… 18 , 25–39 , 47–49 , 51 , 53–57 The 6-month seizure freedom rate was presented in 9/25 studies and varied between 39% and 96% (WA = 60%), 25 , 26 , 30 , 32 , 34 , 37 , 47 , 54 , 55 while the 12-month seizure freedom rate was presented in 4/25 studies, ranging between 68% and 96% (WA = 74%). 31 , 35 , 53 , 54 A seizure reduction rate ≥50% at 6 months was presented in 2/25 studies and varied between 71% and 100% (WA = 82%). 25 , 30 One study reported a seizure reduction rate of ≥50% at 12 months of 97%.…”
Section: Resultsmentioning
confidence: 99%
“… 18 , 25–39 , 47–49 , 51 , 53–57 The 6-month seizure freedom rate was presented in 9/25 studies and varied between 39% and 96% (WA = 60%), 25 , 26 , 30 , 32 , 34 , 37 , 47 , 54 , 55 while the 12-month seizure freedom rate was presented in 4/25 studies, ranging between 68% and 96% (WA = 74%). 31 , 35 , 53 , 54 A seizure reduction rate ≥50% at 6 months was presented in 2/25 studies and varied between 71% and 100% (WA = 82%). 25 , 30 One study reported a seizure reduction rate of ≥50% at 12 months of 97%.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Ius et al. outlined the importance of the EOR on postoperative seizure outcome as the EOR was independent of the molecular class of the tumor ( 58 ). Similarly, Xu et al.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, IFOF and SLF infiltration may not have been relevant. Epileptogenic processes in tumor-related epilepsy (TRE) are multifactorial and not fully understood ( 52 ). Increased evidence suggests that, in up to two-thirds of patients with glioma, seizures arise from the peritumoral cortex, due to induced changes in neurotransmitters, environment and electrical properties of these regions ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%